Science academies issue statement about science and sustainable development. (11th June 2013) - Showstack, Randy
Abstract : In advance of the Group of 8's (G8) 17–18 June meeting of some of the world's leading industrialized nations, 14 science academies have issued a joint statement about how science, technology, and innovation can play a role in driving sustainable development. The statement, issued on 29 May, highlights a number of challenges for bringing an estimated 1.3 billion people out of poverty while also meeting the needs of a soaring world population that is expected to be approximately 9 billion by 2050.